A Census of the Warm‐Core Rings of the Gulf Stream: 1980–2017. Issue 8 (17th August 2020) - Gangopadhyay, Avijit; Gawarkiewicz, Glen; Silva, E. Nishchitha S.; Silver, Adrienne M.; Monim, M.; Clark, Jenifer
Abstract: A census of Gulf Stream (GS) warm‐core rings (WCRs) is presented based on 38 years (1980–2017) of data. The census documents formation and demise times and locations, and formation size for all 961 WCRs formed in the study period that live for a week or more. A clear regime shift was observed around the Year 2000 and was reported by a subset of authors (Gangopadhyay et al., 2019, https://doi.org/10.1038/s41598-019-48661-9 ). The WCR formation over the whole region (75–55°W) increased from an average of 18 per year during Regime 1 (1980–1999) to 33 per year during Regime 2 (2000–2017). For geographic analysis formation locations were grouped in four 5° zones between 75°W and 55°W. Seasonally, WCR formations show a significant summer maxima and winter minima, a pattern that is consistent through all zones and both temporal regimes. The lifespan and size distribution show progressively more rings with higher longevity and greater size when formed to the east of 70°W. The average lifespan of the WCRs in all four zones decreased by 20–40% depending on zones and/or seasons from Regime 1 to Regime 2, while the size distribution remained unchanged across regimes. The ring footprint index, a first‐order signature of impact of the WCRs on the slope, increased significantly (26–90%) for all zones from Regime 1 to Regime 2, with the highest percent increase in Zone 2 (70–65°W). This observational study establishes critical statistical and dynamical benchmarks for validating numerical models and highlights the need for further dynamical understanding of the GS‐ring formation processes. Key Points: The WCR formation from the GS has almost doubled from 1980–1999 to 2000–2017 with a significant upward regime shift in the GS behavior The average lifespan decreased from Regime 1 to Regime 2; while the size remained invariant The overall impact of increasing WCR on the slope is estimated to be about 80% between 75°W and 65°W and 25–60% to the east of 65°W